2010
DOI: 10.1074/jbc.m109.076448
|View full text |Cite
|
Sign up to set email alerts
|

Roscovitine Binds to Novel L-channel (CaV1.2) Sites That Separately Affect Activation and Inactivation

Abstract: L-type (Ca V 1.2) calcium channel antagonists play an important role in the treatment of cardiovascular disease. (R)-Roscovitine, a trisubstituted purine, has been shown to inhibit L-currents by slowing activation and enhancing inactivation. This study utilized molecular and pharmacological approaches to determine whether these effects result from (R)-roscovitine binding to a single site. Using the S enantiomer, we find that (S)-roscovitine enhances inactivation without affecting activation, which suggests mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…Roscovitine has also been shown to affect the activity of ionic channels though a CDK‐independent process, as in the present study for CFTR channels. For example, roscovitine binds to L‐type calcium channels (Yarotskyy et al ., ) and blocks various voltage‐dependent potassium channels (K v 1.3, K v 2.1, K v 4.3 and K v 11.1) by an open‐channel mechanism (Ganapathi et al ., ). Interestingly, unlike other hERG channel blockers, roscovitine is not trapped by hERG channel closing leading to the absence of arrhythmias (Ganapathi et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Roscovitine has also been shown to affect the activity of ionic channels though a CDK‐independent process, as in the present study for CFTR channels. For example, roscovitine binds to L‐type calcium channels (Yarotskyy et al ., ) and blocks various voltage‐dependent potassium channels (K v 1.3, K v 2.1, K v 4.3 and K v 11.1) by an open‐channel mechanism (Ganapathi et al ., ). Interestingly, unlike other hERG channel blockers, roscovitine is not trapped by hERG channel closing leading to the absence of arrhythmias (Ganapathi et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Basic researchers using rodent models of TS have reported that the ablation of the anchoring molecule AKAP150 and inhibition of the calmodulin-dependent protein kinase II (CaMKII) can restore normal functions in Ca V 1.2 channels(3, 4). Yarotskyy et al found that Roscovitine (Ros), a cycline-dependent kinase inhibitor, increased voltage-dependent inactivation of Ca V 1.2 channels and restored normal kinetics in TS Ca V 1.2 channels in HEK 293 cells expressing Ca V 1.2 channel constructs(31, 32). Based on this finding, we investigated whether Ros could restore normal calcium handling in TS cardiomyocytes.…”
Section: Therapeutic Approaches To Tsmentioning
confidence: 99%
“…The conventional L-type calcium channel blocker nimodipine failed to reverse the excess expression of TH in these neurons. Earlier studies in cardiomyocytes 12 from TS individuals indicated that roscovitine 2,3,29 , a cyclin-dependent kinase blocker that also increases L-type channel inactivation, can reduce the prolongation of the cardiac AP in cells from TS individuals. Treatment with roscovitine caused a 68% reduction in the proportion of TH + neurons (Fig.…”
mentioning
confidence: 99%
“…In addition, neurons derived from individuals with Timothy syndrome show abnormal expression of tyrosine hydroxylase and increased production of norepinephrine and dopamine. This phenotype can be reversed by treatment with roscovitine, a cyclin-dependent kinase inhibitor and atypical L-type–channel blocker 2, 3, 4 . These findings provide strong evidence that Ca v 1.2 regulates the differentiation of cortical neurons in humans and offer new insights into the causes of autism in individuals with Timothy syndrome.…”
mentioning
confidence: 99%